Effect of Different Levels of Multienzymes on Immune Response, Blood Hematology and Biochemistry, Antioxidants Status and Organs Histology of Broiler Chicks Fed Standard and Low-Density Diets - Attia, Y. A.; Al-Khalaifah, H.; Abd El-Hamid, H. S.; Al-Harthi, M. A.; El-shafey, A. A. (Frontiers in Veterinary Science, 2020)
This experiment was conducted to study the effect of supplementing three multi-enzyme levels (0, 0.1 and 0.2 g per kg feed) with two types of diet (standard diet, SD, vs low- density diet, LDD) on immune response, blood hematology and biochemistry, antioxidants status, and organ histology of broilers during 1-38 d of age. A total of 216 un-sexed one-day-old Arbor Acres broiler chicks were randomly distributed, on a factorial design (2 × 3), to 6 treatments each with 6 replicates. There were 6 chicks per replicate. Results showed that low-density diet significantly decreased the European Production Efficiency Index (EPEI) by 5.4% throughout the experimental period. Addition of multi-enzymes at both levels (0.1 and 0.2 %) significantly improved EPEI, compared to the control diet. Survival rate, alanine aminotransferase (ALT), aspirate aminotransferase (AST), malondialdehyde (MAD), lymphocyte, lymphocyte transformation test (LTT), and phagocyte activity (PA) were significantly higher for LDD than the SD, but eosinophils was lower. Supplementation of multi-enzymes significantly decreased ALT, AST, MAD, compared to the control group, but increased packed cell volume (PCV), hemoglobin (Hgb), lymphocytes, and monocytes. Immune organs such as spleen, thymus and bursa of Fabricius and immune response to NDV and AI as measured by HI test were significantly increased with multi-enzymes supplementation. Similar results were shown in survival rate during 38-48 days of age after challenge with AI virus at 38 days of age. It could be concluded that multi-enzyme supplementation at either 0.1 or 0.2 g/kg of diet to standard- or low- density diet improved EPEI and immune status of broiler chicks during 1-38 d of age. In addition, LDD diet supplemented with multi-enzymes at 0.1% showed similar immune response to those of the SD without multi-enzymes supplementation. Furthermore, multi-enzyme supplementation to LDD increased survival rate of challenged broilers during days 38-48 of age. Multi-enzyme supplementation at either 0.1 or 0.2 g/kg diet resulted in significantly greater immune organs and higher immune response.